The Effect of Gibberellin (GA3) Concentration on the Growth and Yield of Several Eggplant Varieties (Solanum melongena L.) - Efrilia Lukita Sari; Pangesti Nugrahani; Djarwatiningsih (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Eggplant (Solanum melongena L.) is an important horticultural crop with high economic value and is widely cultivated in various regions due to increasing demand. This study aimed to determine the effects of gibberellin (GA3) concentration and eggplant varieties on the growth and yield of eggplant (Solanum melongena L.). The research was conducted in Kolomayan Village, Wonodadi District, Blitar Regency, from February to May 2025. A Completely Randomized Design (CRD) with a factorial arrangement of two factors was used. The first factor was gibberellin concentration at 0 ppm, 100 ppm, 200 ppm, and 300 ppm. The second factor was the eggplant variety, including Hitavi, Mustang, Pulus, and Teho 555. Parameters observed included vegetative and generative growth traits. The results showed a significant interaction between 200 ppm GA3 concentration and the Hitavi variety on total harvested fruit weight. The 200 ppm GA3 treatment alone produced the best results across all observed parameters. The Teho 555 variety excelled in plant height and leaf number, while the Hitavi variety outperformed others in flower number, total fruit number per plant, total fruit weight per plant, and fruit set.